Enhancing Environmental Awareness through Digital Poster Creation in Elementary School Students - Prastyo, Erwin (Proceeding International Conference on Religion, Science and Education, 2026)
This best practice describes an innovative learning activity that integrates digital literacy, environmental awareness, and moral responsibility through the creation of educational posters. Conducted with 17 sixth-grade students of SD Negeri 1 Curugsewu in the 2023/2024 academic year. This study aimed to develop students’ skills in using digital tools while deepening their understanding of environmental ethics. The learning process involved observing environmental issues, gathering data, designing digital posters, and presenting them to peers. The assessment covered three aspects: digital skills, environmental awareness, and moral responsibility toward nature. The results indicated that most students achieved ‘good’ to ‘excellent’ levels across all aspects, with reflective statements showing that students became more aware of the importance of preserving nature. This practice demonstrates that digital-based creative projects can effectively foster students’ cognitive, emotional, and moral engagement with environmental education.